DETECTION OF EATING DISORDERS IN MALE AND FEMALE ARTISTIC GYMNASTS - Konstantina-Erifyli Papacharalampous; Costas Dallas; George Dallas (University of Ljubljana Press (Založba Univerze v Ljubljani), 2022)
The purpose of this study was to investigate the trend of eating disorders in competitive male and female artistic gymnasts. The study involved 23 male and 42 female gymnasts, aged 7-27, from sports clubs throughout Greece. The EAT-26 Diet Attitudes scale was used to investigate participants' eating habits. The data collection process included communication with sports organizations throughout Greece on the content and purpose of the research. After consultation, the questionnaire was due to the COVID-19 pandemic provided in an electronic form and also included the consent form for participation in the research. The results of the study indicated that eleven of the sixty-five gymnasts had a total score of >20 on the EAT-26, a rate higher among female gymnasts (~ 24%) compared to male gymnasts (~ 4.4%) (p <.05). Although female gymnasts develop more eating disorders and bulimia than male gymnasts, no significant differences were found in the subscales of the questionnaire (p > .05). Therefore, this finding in combination with the fact that most of the gymnasts were teenagers (15.23 ± 6.35 years old) requires particular importance and attention from coaches and the family environment.